Utility Functions That Depend on Health Status: Estimates and Economic Implications - Viscusi, W. Kip; Evans, William N. (American Economic Review, 1990)
Taylor's series and logarithmic estimates of health state-dependent utility functions both imply that job injuries reduce one's utility and marginal utility of income, thus rejecting the monetary loss equivalent formulation. Injury valuations have unitary income elasticity, and the valuation of non-incremental risk changes and effects of base risks follow economic predictions.